Hyaluronan promotes intracellular ROS production and apoptosis in TNFα-stimulated neutrophils - Niemietz, Iwona; Brown, Kelly L. (Frontiers in Immunology, 2023)
Background: Hyaluronan (HA) is an important structural component of the extracellular matrix and has well-described roles in maintaining tissue integrity and homeostasis. With inflammation, HA metabolism (synthesis and degradation) increases and results in higher concentrations of soluble HA. Previously, we demonstrated that (soluble) HA primed resting neutrophils for the oxidative burst in response to a secondary stimulus. Notably, HA-mediated priming was not dependent on degranulation, which is a hallmark of priming by classical agents such as TNFα. In this study, we queried the ability of HA to prime neutrophils to different stimuli and its capacity to modulate neutrophil function in the presence of TNFα. Methods: Blood neutrophils from healthy donors were stimulated ex vivo with HA in the absence and presence of classic neutrophil agonists, inclusive of TNFα. Western blotting was used to assess the activation (phosphorylation) of p38 MAPK, and key neutrophil functions associated with priming and activation, such as intracellular and extracellular ROS production, degranulation, and apoptosis, were evaluated by standard chemiluminescence assays (ROS) and flow cytometry. Results: Hyaluronan is capable of atypical priming and, with TNFα, co-priming neutrophils for an enhanced (rate and/or magnitude) oxidative burst to various secondary stimuli. In addition, HA can augment intracellular ROS production that is directly induced by TNFα in resting neutrophils, which coincided with the activation of p38 MAPK and apoptosis. Conclusions: These data demonstrate that the extracellular matrix component HA is a key modulator of neutrophil function(s) in the presence of inflammatory agents such as TNFα. Moreover, it provides additional evidence for the diversity and complexity of neutrophil priming and activation during inflammation.